Antiadhesive nanosome elicits role of glycocalyx of tumor cell-derived exosomes in the organotropic cancer metastasis. (January 2022) - Koide, Ryosuke; Hirane, Nozomi; Kambe, Daiki; Yokoi, Yasuhiro; Otaki, Michiru; Nishimura, Shin-Ichiro
Abstract: Despite emerging importance of tumor cells-derived exosomes in cancer metastasis, the heterogeneity of exosome populations has largely hampered systemic characterization of their molecular composition, biogenesis, and functions. This study communicates a novel method for predicting and targeting pre-metastatic sites based on an exosome model "fluorescent cancer glyconanosomes" displaying N -glycans of cultured tumor cells. Glycoblotting by antiadhesive quantum dots provides a nice tool to shed light on the pivotal functions of the glycocalyx reconstructed from four cancer cell types without bias due to other compositions of exosomes. In vivo imaging revealed that circulation, clearance, and organotropic biodistribution of cancer glyconanosomes in mice depend strongly on cancer cell-type-specific N-glycosylation patterns, the compositions of key glycotypes, particularly dominant abundances of high mannose-type N -glycans and the position-specific sialylation. Notably, organ biodistribution of cancer glyconanosomes is reproducible artificially by mimicking cancer cell-type-specific N-glycosylation patterns, demonstrating that nanosomal glycoblotting method serves as promising tools for predicting and targeting pre-metastatic sites determined by the glycocalyx of extracellular vesicles disseminated from the primary cancer site.